Social Entrepreneurship: Does Institutional Environment Make a Difference? - José Cadima Ribeiro; José Freitas Santos; Susana Bernardino (European Regional Science Association (ERSA), 2015)
Social entrepreneurship has been recognized as a helpful instrument of social and economic policy. The European Commission, namely, has recognized very early the importance of social organizations on economic growth and social innovation, through their contribution for the development of societies endowed with better levels of democracy, activism and social cohesion. Having that in mind, the purpose of this paper is to contribute to a better understanding of the link between social entrepreneurship and institutional environment in Portugal. A quantitative approach is used in the study, and primary data were collected through an online survey. A questionnaire was emailed to, both, Portuguese Non-Governmental Organizations and projects available on the Portuguese Social Stock Exchange. In the analysis of the data we used descriptive statistics, factorial analysis and t-student tests to validate (or not) the research hypotheses. The results show that a favorable institutional environment (social, institutional) seems to have a low influence on the decision-making process related to the creation of new social entrepreneurial initiatives. Conversely, the sense individuals hold about the skills required to develop the new venture and the previous knowledge that their action will produce a desirable outcome have a significant weight on their decision. This conclusion supports the idea that many social entrepreneurs can emerge even in developing regions where the institutional environment is weak. Therefore, social entrepreneurship could be an instrument of regional development and contribute to attenuate the social and economic differences among Portuguese regions.
Keywords: R11; 330; Social Entrepreneurship; Social and Solidarity Economy; Regional Development